Pengaruh Latihan Triceps Dips dan Dumble Extension terhadap Kekuatan Otot Lengan Atlet Bola Voli - Wati, Merita Efina; Pelamonia, Shandy Pieter (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to examine the effects of Tricep Dips and Dumbbell Extension exercises on improving arm muscle strength among volleyball athletes participating in extracurricular activities at SMAN 1 Wringinanom Gresik. A quantitative approach was employed using a Control Group Design, involving 20 athletes as research subjects. Data were collected through a one-minute push-up test to measure upper arm strength. Data analysis was conducted using multiple regression tests with the assistance of SPSS version 24. The results revealed that both types of exercises had a significant impact on arm muscle strength. This was evidenced by the significance values of 0.047 for the Tricep Dips group and 0.008 for the Dumbbell Extension group (p < 0.05). Therefore, it can be concluded that Tricep Dips and Dumbbell Extension exercises significantly contribute to enhancing arm muscle strength among volleyball athletes at SMAN 1 Wringinanom Gresik.